Visual Hebb Repetition Effects: The Role of Psychological Distinctiveness Revisited - Johnson, Andrew J.; Miles, Christopher (Frontiers in Psychology, 2019)
Across two experiments we investigate the role of psychological distinctiveness on the Hebb repetition effect. In direct contradiction to Horton et al. (2008), Experiment 1 demonstrated the Hebb repetition effect for inverted faces. Importantly, the Hebb repetition effect was evident only when the filler and Hebb sequences comprised different items (no-stimulus-overlap) and was abolished when the filler and Hebb trials comprised the same items (full-stimulus-overlap). Experiment 2 further examined the impact of psychological distinctiveness on the Hebb repetition effect by comparing serial recall for upright unfamiliar-faces, inverted unfamiliar-faces, and abstract matrices. We demonstrate the visual Hebb repetition effect for stimuli that possess both purportedly high (upright faces) and low (inverted faces and matrices) levels of psychological distinctiveness. The findings of both experiments contradict the earlier claim (Horton et al., 2008) that stimuli possessing low levels of psychological distinctiveness do not show the visual Hebb repetition effect. However, we further highlight the importance of stimulus overlap between filler and Hebb sequences in determining the visual Hebb repetition effect. More generally, our findings emphasise that the Hebb repetition effect is a common feature of memory across different stimulus types.